Stereotactic ablative radiation for pancreatic cancer on a 1.5 Telsa magnetic resonance-linac system - Tringale, Kathryn R.; Tyagi, Neelam; Marsha Reyngold; Romesser, Paul B.; Wu, Abraham; O'Reilly, Eileen M.; Varghese, Anna M.; Godoy Scripes, Paola; Khalil, Danny N.; Park, Wungki; Yu, Kenneth; Crane, Christopher H. (Physics and imaging in radiation oncology, 2022)
•Ablative radiation therapy (A-RT) is effective for locally advanced pancreas cancer.•30 patients received A-RT using diagnostic quality MR-adaptive treatment delivery.•Cumulative incidences of 1-year local and distant progression were 19.3% and 47.4%•Overall and progression-free survival 1-year from A-RT was 80.0% and 39.7%•50 Gray in 5 fractions led to promising 1-year local control and survival.•Most local failures were marginal at the tumor-organ-at-risk (OAR) interface.•No grade 3 or higher toxicities were observed despite adjacent sensitive OARs. Ablative radiation therapy (A-RT) appears to improve outcomes in locally advanced pancreatic cancer (LAPC) yet requires solutions for respiratory and digestive motion. We report outcomes of A-RT for pancreatic cancer using 1.5 T MR-adaptive treatment delivery. Between March 2020 and July 2021, we treated 30 patients with pancreatic cancer with 50 Gy in 5 fractions (biologically effective dose [BED10] = 100 Gy10) using a novel compression belt workflow and remote planning on the Unity 1.5 T MR linac system. Cumulative incidence of progression was computed from A-RT initiation with death as a competing risk. Overall (OS) and progression-free survival (PFS) were calculated using Kaplan Meier methods. Of 30 patients, most (73 %) were locally advanced, 4 (13 %) were metastatic, 2 (7 %) were medically inoperable, and 2 (7 %) were locally recurrent. Most (73 %) received FOLFIRINOX prior to A-RT. Median follow-up times from diagnosis and A-RT were 17.6 (IQR 15.8–23.1) and 11.5 months (IQR 9.7–16.1), respectively. Cumulative incidences at 1-year of local and distant progression were 19.3 % (95 %CI 6.7–36.8 %) and 47.4 % (95 %CI 26.7–65.6 %), respectively. Median OS from diagnosis and A-RT were not reached. One-year OS from diagnosis and A-RT were 96.4 % (95 %CI 77.2–99.5 %) and 80.0 % (95 %CI 57.3–91.4 %), respectively. Median and 1-year PFS were 10.1 months (95 %CI 4.4–14.4) and 39.7 % (95 %CI 20.3–58.5 %), respectively. No grade 3 + toxicities were observed. A-RT using the 1.5 T Unity MR Linac resulted in promising LC and OS with no severe toxicity in patients with LAPC despite radiosensitive organs adjacent to the target volumes. Longer follow-up is needed to assess long-term outcomes.